Simple Cash Flow Management Training to Prevent Financial Distress Among KSBI Micro-Entrepreneurs in South Jakarta - Muhammad Zilal Hamzah; Eleonora Sofilda; Dida Nurhaida (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
Micro-entrepreneurs in Indonesia, particularly those in the informal sector, often face difficulties in financial management because of limited knowledge of basic cash flow practices. To address this issue, a community engagement program was conducted for members of Komunitas Sukses Berjamaah Indonesia (KSBI) in South Jakarta, with a focus on simple cash flow management training. Using a Participatory Action Research (PAR) approach, the program involved 25 micro-entrepreneurs through the stages of diagnosis, action, evaluation, and reflection. The training modules covered income and expense tracking, cash flow forecasting, and emergency fund planning. Pre-and post-test results showed a significant improvement in participants’ financial literacy, with the overall mean score increasing from 54.5 to 85.3. Participant feedback also indicated strongly positive responses, with 95% reporting an improved ability to separate personal and business finances and all participants expressing greater confidence in making financial decisions. In addition, 85% of participants planned to build emergency savings after the training. Overall, the program strengthened basic financial management skills and encouraged more structured financial practices among micro-entrepreneurs.